2020
DOI: 10.3390/ijerph17197337
|View full text |Cite
|
Sign up to set email alerts
|

Association between Perceived Oral Symptoms and Presence of Clinically Diagnosed Oral Diseases in a Sample of Pregnant Women in Malaysia

Abstract: The integration of oral health into primary health care denotes the important role of medical counterparts as the front liners in antenatal care to help screen mothers for oral symptoms and refer them to dentists accordingly. However, the validity of self-perceived oral health status is inconclusive. This study determined the association between self-perceived oral symptoms and the presence of clinically diagnosed oral diseases in a sample of pregnant women. A total of 192 pregnant women participated in this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 22 publications
1
26
3
2
Order By: Relevance
“…The second most frequent problem pregnant women reported was the increased salivation (77.30%) followed by burning sensation during swallowing (34.50%) of the preganant women population. Yunita et al [2] did a study on a sample of pregnant women in Malaysia but half of that study population reported dental caries , followed by bleeding gums. This difference in both studies results can be attributed to the fact that Pakistan is underdeveloped country and patients don't have access to basic oral health care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second most frequent problem pregnant women reported was the increased salivation (77.30%) followed by burning sensation during swallowing (34.50%) of the preganant women population. Yunita et al [2] did a study on a sample of pregnant women in Malaysia but half of that study population reported dental caries , followed by bleeding gums. This difference in both studies results can be attributed to the fact that Pakistan is underdeveloped country and patients don't have access to basic oral health care.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy results in increased secretion of estrogen and progesterone which leads to various changes in body organs including oral cavity [2].Poor oral hygiene and hormonal changes can lead to gingivitis, periodontitis, benign lesions like pregnancy tumors and increases susceptibility to oral infections [3].These hormonal changes may also contribute to change in salivary p [4,5] in turn, leading to increased incidence of dental caries [6]. Modi cation in diet and frequency of eating can increase the risk of developing tooth decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salienta-se que não foram encontrados na literatura estudos sobre as taxas do uso do serviço odontológico por gestantes de alto risco. Em pesquisas realizadas, a demanda de gestantes, em geral, por serviços odontológicos variou de 29% a 42% (MARCHI et al, 2019;YUNITA SARI;SADDKI;YUSOFF, 2020).…”
Section: Discussionunclassified
“…Risk factors are chronic gingivitis, inadequate oral hygiene, antihypertensive, use of hormonal therapies, antiepileptic, immunosuppressive drugs in pregnancy [31]. Clinicians must be conscious of higher gingival inflammation measures may be found in women who have a higher body mass index [32].…”
Section: Periodontal Conditions During the Pregnancymentioning
confidence: 99%